Investigation of the effects of biggame-preserves on forests with different species composition - Győri, Judit; Rédei, Károly; Juhász, Lajos; Szendrei, László (Acta Agraria Debreceniensis, 2012)
Hungary is well known for its high level game management. In order to develop a concentrated and more profitable gamemanagement new game preserves were established in the last few years. According to the law, in the game-preserves the game bearing capacity is not the most important parameter, because in these areas the feeding is continuous. In practice it means that in gamepreserves we find a much higher density of games than in nature. This causes a relative big loading of the area (of the herbaceous and arboreal), where the game-preserves are located.Our aim is to study the ecological and management issues of forest- and game resources. The scene of these work is a gamepreserves related to the Nyírerdő Corporation (Nyíregyháza). We made forest structure survey to determine the main stand-forming tree species in the area of the game preserves as well as to estimate the number of the measuring points.